Pelatihan Materi KSN-Geografi Untuk Guru Geografi SMA Negeri Kabupaten Bogor - Muzani Muzani; Suhardjo Suhardjo; Warnadi Warnadi (Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2021)
To achieve better achievements in KSN, various preparation efforts are needed, including mastering the material for HOTS questions or higher order thinking skills, namely questions with higher-order thinking skills that will definitely be tested well in KSN. Teachers in schools play a very important role in facilitating and directing their students to become champions at the National level, because: (1). Teachers at school are the ones who understand and understand the condition of their students, always interacting every day. The teacher is also the one who will really know the potential that is in each student. (2). Teachers at schools really understand how the learning attitudes, mental, psychological and various characteristics of each student certain concepts. In order for the important role of this teacher to be maximized, of course, the teacher must also receive guidance and training, because (a) Not all teachers know how to use the strategy to